A model of working from home (WFH) concept in Malaysian construction industry. - Hassan, Hasnanywati (Universiti Sains Malaysia, 2014)
Working from home concept has been introduced for decades and is commonly practiced by many industries in Western and European countries but the awareness of working from home among industries in Malaysia is still very weak especially in the construction industry. Working from home is known to serve better work-life advantages to the company and employee such as real-estate cost savings, productivity increase, less absenteeism, labour relations flexibility, better customer service, flexibility and cost savings in commuting. Working from home is seen as one of the new business cultures for quantity surveying firms to execute and presume to survive in construction industry. Therefore the determinants of working from home and their relationship towards firm's benefits have to be investigated.